Ex‐ante evaluation of promising soybean innovations for sub‐Saharan Africa. (16th May 2019) - Gbegbelegbe, Sika; Alene, Arega; Kamara, Alpha; Wiebe, Keith; Manyong, Victor; Abdoulaye, Tahirou; Mkandawire, Petros
Abstract: This study undertakes an ex‐ante evaluation of the effects of alternative technology and policy options on soybean supply and demand in sub‐Saharan Africa (SSA) to 2050. Current soybean consumption in SSA is dominated by cooking oil followed by soybean cake used as animal feed. Due to weak processing sectors and low soybean yields, the region is currently importing about 70% of its consumption requirements. Based on the results from a geospatial bio‐economic modeling framework, soybean consumption in SSA is projected to more than double by 2050 compared to 2010 due in part to a rising population and rising incomes. On the other hand, supply from domestic production is projected to increase by 80% over the same period. Hence, by 2050, net imports into SSA would be nearly 4 times higher than supply from domestic production. Under a future drier climate, some of the production gains achieved through soybean research and extension would be lost and this would further worsen the soybean demand gap in SSA relative to the baseline. This study shows that relying on conventional breeding alone to increase soybean yields in SSA would not be enough to substantially reduce the future demand gap. A combination of promising innovations affecting the soybean value chain across SSA would be needed to close the soybean demand gap in SSA by 2050 under a drier future climate. Abstract : Sub‐Saharan Africa currently spends more than US 1 billion on net imports of soybean‐based agricultural products. The soybean demand gap for this region is projected to increase in the future. This study shows that a combination of promising innovations affecting the soybean value chain across SSA would be required to close the future soybean demand gap.